Haiti : Fourth Review Under the Extended Credit Facility: Staff Report and Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper discusses key findings of the Fourth Review Under the Extended Credit Facility (ECF) for Haiti. All end-March 2012 performance criteria were met. Implementation of structural reforms has also continued, although two out of three end-March 2012 structural benchmarks were not observed. The stance of macroeconomic policy and the reform agenda remain broadly unchanged, and will continue to focus on consolidating macroeconomic stability, mobilizing higher revenue to allow increased spending in critical areas and strengthening cash management. Structural reforms will also seek to modernize the financial sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet